Targeting the Aryl Hydrocarbon Receptor Signaling Pathway in Breast Cancer Development - Vogel, Christoph F. A.; Lazennec, Gwendal; Kado, Sarah Y.; Dahlem, Carla; He, Yi; Castaneda, Alejandro; Ishihara, Yasuhiro; Vogeley, Christian; Rossi, Andrea; Haarmann-Stemmann, Thomas; Jugan, Juliann; Mori, Hidetoshi; et al. (Frontiers in Immunology, 2021)
Activation of the aryl hydrocarbon receptor (AhR) through environmental exposure to known human carcinogens including dioxins can lead to the promotion of breast cancer. While the repressor protein of the AhR (AhRR) blocks the canonical AhR pathway, the function of AhRR in the development of breast cancer is not well known. In the current study we examined the impact of suppressing AhR activity using its dedicated repressor protein AhRR. AhRR is a putative tumor suppressor and is silenced in several cancer types, including breast, where its loss correlates with shorter patient survival. Using the AhRR transgenic mouse, we demonstrate that AhRR overexpression opposes AhR-driven and inflammation-induced growth of mammary tumors in two different murine models of breast cancer. These include a syngeneic model using E0771 mammary tumor cells as well as the Polyoma Middle T antigen (PyMT) transgenic model. Further AhRR overexpression or knockout of AhR in human breast cancer and mouse mammary tumor cells enhanced apoptosis induced by chemotherapeutics. This study provides the first in vivo evidence that AhRR suppresses mammary tumor development and suggests that strategies which lead to its functional restoration and expression may have therapeutic benefit.